Photodynamic inactivation of oropharyngeal Candida strains - Postigo, Agustina (2014)
Oropharyngeal candidiasis (OPC) is an infection frequent in immunocompromised patients. Photodynamic therapy is an alternative to conventional treatments, based on the utilization of compounds that inhibit or kill microorganisms only under the effect of light, process known as Photodynamic Inactivation (PDI). In the present study, PDI of Candida spp. by the natural product α-terthienyl (α-T) was investigated following the guidelines of CLSI M27-A3, under UV-A light irradiation. The optimal values of two variables, exposure irradiation time (ET) and distance to the irradiation source (DIS) were established by employing Design Expert Software (DES). For this purpose, a panel of Candida strains isolated from OPC (C. albicans, C. tropicalis, C. parapsilosis and C. krusei) was employed and optimal values were 5 min (ET) and between 6.06 and 6.43 cm (DIS) with a desirability factor of 0.989. α-T plus UV-A light in the optimal conditions caused a complete reduction in viable cells in 5 min which was demonstrated by viable cells reduction assays and confocal microscopy after vital staining (propidium iodide/fluorescein diacetate). The germ tube formation of C. albicans was inhibited by α-T at sub-inhibitory concentrations. Results showed that α-T plus UV-A light could constitute an alternative for OPC treatments at the optimal conditions determined here